THE INFLUENCE OF E-SERVICE QUALITY AND CUSTOMER SATISFACTION TOWARDS REPURCHASE INTENTION TO USE EWALLET (A STUDY ON SHOPEEPAY INDONESIA) - Edmil, Amelia Nurmawati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2021)
This study aimed to determine the influence of fulfillment, customer service, security & privacy, application design, and customer satisfaction on Shopee Pay’s repurchase intention. The type of research is an associative study that explains the relationship and influence between one variable and another through hypothesis submission. This study used a sample of 100 respondents by distributing questionnaires online. The sample consisted of respondents who have done payment using ShopeePay at least twice a year dan acknowledge the feature and facilities of ShopeePay. Data was analysed using multiple regression analysis using the SPSS Version 25. The results of testing the five hypotheses concluded that the fulfillment, customer service, security & privacy, application design, and customer satisfaction respectively, have a significant effect on ShopeePay’s repurchase intention.Keywords: Fulfillment, Customer Service, Security & Privacy, Application Design, Customer satisfaction, Repurchase Intention